Smoking Cessation Alters Intestinal Microbiota: Insights from Quantitative Investigations on Human Fecal Samples Using FISH - Biedermann, Luc; Brülisauer, Karin; Zeitz, Jonas; Frei, Pascal; Scharl, Michael; Vavricka, Stephan R.; Fried, Michael; Loessner, Martin J.; Rogler, Gerhard; Schuppler, Markus (Inflammatory bowel diseases, 2014)
There has been a dramatic increase in investigations on the potential mechanistic role of the intestinal microbiota in various diseases and factors modulating intestinal microbial composition. We recently reported on intestinal microbial shifts after smoking cessation in humans. In this study, we aimed to conduct further microbial analyses and verify our previous results obtained by pyrosequencing using a direct quantitative microbial approach.MethodsStool samples of healthy smoking human subjects undergoing controlled smoking cessation during a 9-week observational period were analyzed and compared with 2 control groups, ongoing smoking and nonsmoking subjects. Fluorescence in situ hybridization was applied to quantify specific bacterial groups.ResultsIntestinal microbiota composition was substantially altered after smoking cessation as characterized by an increase in key representatives from the phyla of Firmicutes (Clostridium coccoides, Eubacterium rectale, and Clostridium leptum subgroup) and Actinobacteria (HGC bacteria and Bifidobacteria) as well as a decrease in Bacteroidetes (Prevotella spp. and Bacteroides spp.) and Proteobacteria (β- and γ-subgroup of Proteobacteria).ConclusionsAs determined by fluorescence in situ hybridization, an independent direct quantitative microbial approach, we could confirm that intestinal microbiota composition in humans is influenced by smoking. The characteristics of observed microbial shifts suggest a potential mechanistic association to alterations in body weight subsequent to smoking cessation. More importantly, regarding previously described microbial hallmarks of dysbiosis in inflammatory bowel diseases, a variety of observed microbial alterations after smoking cessation deserve further consideration in view of the divergent effect of smoking on the clinical course of Crohn's disease and ulcerative colitis.